Understanding Racial Disparities in Prostate Cancer: A Multifaceted Approach - Charles Cobbs IV; Gregory T. Chesnut; Ayesha A. Shafi (Cancer Medicine)
ABSTRACT Prostate cancer (PCa) remains a significant public health challenge in the United States, disproportionately affecting African American (AA) men, who face higher incidence rates, more aggressive disease, and elevated mortality compared to Caucasian American (CA) men. This review explores the multifactorial underpinnings of these disparities, integrating genomic, socioeconomic, environmental, and systemic contributors. Genomic analyses reveal that AA men harbor distinct molecular alterations, including higher frequencies of FOXA1, BRAF, and CHD1 mutations, as well as DNA damage repair defects, highlighting the critical need for population‐specific precision medicine. Immune‐oncologic pathways and stromal interactions within the tumor microenvironment further underscore biological differences driving aggressive disease phenotypes. Concurrently, adverse social determinants—including limited access to care, lower PSA screening rates, delayed treatment, medical mistrust, and underrepresentation in clinical trials—contribute to poorer outcomes. Despite these challenges, evidence from equal‐access healthcare systems indicates that when provided equitable treatment, AA men can achieve outcomes comparable to or better than their CA counterparts. This review emphasizes actionable strategies to reduce disparities, including increasing AA representation in clinical trials, enhancing culturally competent patient‐provider communication, improving access to early detection and high‐quality care, and expanding community‐based outreach initiatives. A holistic, interdisciplinary approach is essential to dismantle systemic barriers and achieve health equity in prostate cancer outcomes.